2019
DOI: 10.3390/medicina55110749
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrothermal Aging and Beverages on Color Stability of Lithium Disilicate and Zirconia Based Ceramics

Abstract: Background and Objectives: All-ceramic prosthesis is widely used in modern dental practice because of its improved physico-mechanical and optical properties. These restorations are exposed to coloring agents from various nutrition and beverages in the oral cavity. Long-term color stability is critical for the success of these restorative materials. The purpose of this in vitro study was to assess the effect of common beverages and mouthwash on the color stability of lithium disilicate (LD), monolithic zirconia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 40 publications
5
44
0
1
Order By: Relevance
“…the absence of a monoclinic phase, this color change may be attributed to the dissolving of glaze in an aggressive medium, which in turn affects the perception of optical properties (32)(33)(34). An amorphous material, glaze, is not resistant to aggressive external influences nor is it chemically stable (33)(34)(35). In an aggressive medium, surface ions in the glaze perish, which leads to irregularities (secondary porosity) that augment roughness -a finding that corresponds to the findings of other authors (32-34).…”
Section: Raspravasupporting
confidence: 63%
“…the absence of a monoclinic phase, this color change may be attributed to the dissolving of glaze in an aggressive medium, which in turn affects the perception of optical properties (32)(33)(34). An amorphous material, glaze, is not resistant to aggressive external influences nor is it chemically stable (33)(34)(35). In an aggressive medium, surface ions in the glaze perish, which leads to irregularities (secondary porosity) that augment roughness -a finding that corresponds to the findings of other authors (32-34).…”
Section: Raspravasupporting
confidence: 63%
“…These results can be related with their colorless nature and no distinguishable color difference occurred. Due to the new focus, there are only few research that consider the effects of green tea on color stability of dental materials like lithium disilicate,zirconia based ceramics and composite resin etc [43,44]. But there is no study about the post-bleaching applications.…”
Section: Discussionmentioning
confidence: 99%
“…Following the 28-day study period, GB specimens stored in the coffee solution showed marked changes compared to other specimens. Similarly, for zirconia specimens immersed in the coffee solution in previous studies, higher than clinically acceptable values were reported [15][16].…”
Section: Discussionmentioning
confidence: 65%
“…The current study evaluated the effect of grit-blasting on the color stability of zirconia ceramics following exposure to common beverages. Although previous studies have evaluated the color stability of zirconia ceramics, this is the first attempt to study the effect of grit blasting on the color stability of zirconia [15][16][17][18]. This was important because the acid-resistant polycrystalline structure of zirconia is resistant to etching and results in weak bonding to resin composites [4].…”
Section: Discussionmentioning
confidence: 99%